The Effect of The Self Regulated Learning Model on Students' Learning Independence During The Covid 19 Pandemic : Pengaruh Model Self Regulated Learning Terhadap Kemandirian Belajar Siswa Selama Masa Pandemi Covid 19 - Eka Nuril Agustina; Akhtim Wahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine whether there is an effect of the self-regulated learning model on student learning independence during the COVID-19 pandemic in grade 4 SDN Kedung Solo Porong. This type of research is a quantitative experiment with the type of pre-experimental designs in the form of one-group pretest-posttest design. The instrument in this study uses pretest and posttest questionnaire instruments. The samples in this study were 4th grade students at SDN Kedung Solo. The results showed that there was an effect of the self-regulated learning model on students' independent learning which was obtained t count = 4.415, so the t table was 2.040. Because 4,415 > 2,040 Ho is rejected and Ha is accepted, it means that there is a significant difference. The calculation of the large influence test shows that 0.69 > 0.14 which interprets the self regulated learning model on student learning independence during the covid 19 pandemic in grade 4 SDN Kedung Solo Porong by 48.59 % in the category of big influence. Highlights: The self-regulated learning model significantly improves student learning independence during the COVID-19 pandemic. Grade 4 students at SDN Kedung Solo Porong benefited from the self-regulated learning approach. The self-regulated learning model had a substantial impact, influencing student learning independence by 48.59%. Keywords: self-regulated learning, student learning independence, COVID-19 pandemic, grade 4, SDN Kedung Solo Porong